The impact of physical activity on cognitive functions - Sylwia Sumińska (Nofer Institute of Occupational Medicine, 2021)
In recent decades we have observed a progressive aging of the society. A growing number of elderly people is associated with an increase in the percentage of people whose cognitive functions are decreasing. It is important to counteract this process and develop lifestyle recommendations that will allow to delay the process of cognitive decline. Regular physical activity has a beneficial effect on health and cognitive performance, especially on executive functions. Data shows the positive impact of physical exercise, both aerobic and resistance training, and their combination, on cognitive performance. Potential biological mechanisms that may underlie the effectiveness of physical exercise include increased blood flow through the brain, changes in the release of neurotransmitters, and the process of neurogenesis. The aim of the article is to analyze the recent research taking into account the relationship between physical activity and cognitive skills. The research published in 2015-2020 was analyzed. The review concerns the effect of physical activity, not a combination of cognitive training and physical exercise, on cognitive skills in a group of healthy adults and the elderly. Studies that defined physical activity as sports, as well as increasing daily activity to reduce a sedentary lifestyle, were analyzed. The analysis of the available data indicates that researchers report positive effects of increasing physical activity on cognitive performance, mainly executive functions (e.g., working memory), but also attention and memory. Only a few studies have not reported any significant differences. However, the analysis of the research shows the lack of uniform methods of measuring the intensity of physical activity, as well as efficiency of cognitive functions. More research is needed to examine the long-term effects. Another study should be conducted to present the most effective intervention techniques and prepare recommendations for maintaining preserved cognitive functions. Further research should be conducted to control variables that affect the acquisition of cognitive skills and cognitive effectiveness during the intervention. Med Pr. 2021;72(4):437-50